A Comparative Needs Analysis of English Communication Skills in Public and Private Sector Administration: Insights from Practitioner Teaching in Batch 4 - Nabilah, Nada (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2025)
In an increasingly globalized administrative landscape, English communication skills have become essential for professionals across public and private sectors. However, the communicative functions and expectations in each domain differ considerably. This study aims to compare the specific English communication needs of public and private sector administration, incorporating insights from practitioner-teachers and students in public administration and management programs. Using a comparative qualitative approach, data were collected through semi-structured interviews and classroom observations involving over ten professionals and educators, alongside student participants. Thematic analysis revealed distinct patterns: public sector communication focuses on formal documentation and bureaucratic clarity, while the private sector emphasizes interactive, client-facing communication. Despite these differences, both sectors share foundational skill demands such as meeting participation and professional writing. Furthermore, practitioner-teachers were found to enhance instructional relevance by integrating real-world experience into ESP classrooms. The study concludes that English instruction in administrative education should be tailored to reflect sector-specific needs and supported by practice-informed pedagogy.